Has the Risk and Value of Firm Infeluenced by Foreign Currency Derivatives? A Case Study of Conventional Banks from Pakistan (Journal of Asian Development Studies, 2020)
Purpose of the study is that is there any effect of using foreign currency derivative on the risk or the value of the firm under the effect of firm risk. The study also assesses scientifically the effect of subordinate use firm risk and firm value in the business of banks in Pakistan. Present study comprises of analyzing the impact of foreign currency derivative utilization on firm value of conventional banks of Pakistan for the time of 2014-2020. Study theorized that conventional banks are utilizing financial derivatives for avoiding risk, use of foreign currency derivatives builds firm value or not.Findings of the study describes that the Conventional banks in Pakistan are using the foreign currency derivatives to avoiding the risk as they use the respective derivatives to increase their firm value. Study also indicate that the market of derivatives is still un-established in Pakistan So, the firms cannot bear the higher trading cost of respective derivatives in state of higher risk which limits the value increasing incentives of derivative usageThe study provides fresh insights on value reliance of foreign currency derivative usage.